Seismic Design Evaluation of T Shaped Irregular Rc Building Plans By Using Pushover Analysis - Necati Mert; Alexis Nzapfakumunsi (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
This study has been conducted to find out howTurkish Seismic Code 2007 is effective in providing the Life Safety (LS) andPerformance Level (PL) of T shaped plan irregularities reinforced concretemulti-story buildings; with special lateral loads bearing moment frame systems.For this purpose, a set of 12 multi-story residential buildings: 3- rectangularplans as reference and their respective 9- different T shaped plans of 3-, 6-and 8- stories were considered in the North Anatolian Fault Zone (NAFZ) Turkeyand were designed based on the code. Then, a modal and a static non-linearpushover analysis were conducted for all buildings. Base shear forces and roofsdisplacement for each building were computed. Besides, the formation trend ofplastic hinges and their respective distribution in the entire buildings wereinspected for evaluating the seismic performances. Results show that for somebuildings the expected performance level which is LS has been overreached andeven in some cases buildings reach the collapse prevention level. Based onthis, it seems that the code provisions still require further upgrading tocreate enough confidence in the civil engineering community.